Counteranion-mediated efficient iodine capture in a hexacationic imidazolium organic cage enabled by multiple non-covalent interactions - Yang, Jian; Hu, Shao-Jun; Cai, Li-Xuan; Zhou, Li-Peng; Sun, Qing-Fu (Nature communications, 2023)
Developing efficient adsorbents to capture radioactive iodine produced from nuclear wastes is highly desired. Here we report the facial synthesis of a hexacationic imidazolium organic cage and its iodine adsorption properties. Crucial role of counteranions has been disclosed for iodine capture with this cage, where distinct iodine capture behaviors were observed when different counteranions were used. Mechanistic investigations, especially with the X-ray crystallographic analysis of the iodine-loaded sample, allowed the direct visualization of the iodine binding modes at the molecular level. A network of multiple non-covalent interactions including hydrogen bonds, halogen bonds, anion···π interactions, electrostatic interaction between polyiodides and the hexacationic skeleton of the cage are found responsible for the observed high iodine capture performance. Our results may provide an alternative strategy to design efficient iodine adsorbents. The development of efficient adsorbents to capture iodine originating from radioactive wastes is of importance. Here, the authors synthesize hexacationic imidazolium organic cages and study the crucial role of the counter anions for iodine capture and the iodine binding modes at the molecular level on the solid state.